Surrealist Works in 21st-Century Prose (Eurasian Journal of Philology Science and Education, 2026)
The article examines surrealist works written in contemporary Kazakh prose. The analyzed works demonstrate a striving for new modes of writing, an expansion of thematic range, psychological depth, linguistic and structural experimentation, and a tendency to present national values from a new aesthetic perspective. The objects of the study include the novella “Қыпшақ аруы” (“The Kipchak Maiden”) by Mukhtar Magauin, the work “Тұтқын” by Roza Mukanova, the short story “Қылбұрау” by Talaptan Akhmetzhanov, “Жазушы жазбасы” (“Writer’s Notes”) by Almaz Myrzakhmet, “Бөтен” (“The Stranger”) by Kolganat Murat, and the novel “Үлкен үйдегі үрей” (“Fear in the Big House”) by Saule Doszhan. The aim of the study is to identify works of a surrealistic nature in twenty-first-century Kazakh prose and to analyze the artistic function of dreams, visions, hallucinations, mystical, and irrational representations in these texts. In accordance with this aim, the objectives were to determine the main features of surrealist poetics, examine them comparatively within a set of specific works, and demonstrate their connection with the artistic explorations of contemporary Kazakh prose. The study determines the specifics of surrealist works, emphasizing the depiction of societal crises through the characters' dreams and visions, introducing a sense of anxiety and fear into the reader’s consciousness.Keywords: surrealism, dream, vision, surrealist layers, contemporary Kazakh prose.